Muscle Energy Technique Effects On Pain, Cervical Range of Motion, and Functional Disability: Life Science-Physiotherapy - Kino, Ayang; Dutta, Abhijit; Mahato, Pompy; Kalita, Abhijit (International Journal of Life Science and Pharma Research, 2023)
An unfavorable sensory or emotional encounter connected to actual or potential tissue injury is referred to as neck pain, and it affects the region of the neck between the superior nuchal line and the first thoracic spinous process. Mechanical neck pain often commences insidiously and is of multifactorial etiology, causing disability and clinical symptoms. It is a comparative study where 30 male and female subjects were assessed and identified with Mechanical Neck Pain, recruited for the study, and randomly divided into two groups with 15 subjects in each group. Outcome measures were the Visual Analogue Scale (VAS), goniometer, and neck disability index (NDI). Pre-Test and Post-Test were carried out for both groups and analyzed using paired 't-tests and independent 't-tests in an IBM SPSS statistics 26 software. This study aimed to compare the effectiveness of muscle energy technique with conventional therapy vs. kinesio taping with conventional therapy in chronic mechanical neck pain, cervical range of motion, and functional disability of the neck. KT provides sensory feedback, tension, and afferent stimulation to reduce pain and improve ROM. It also helps in lymphatic and vascular flow and corrects misaligned structures. Muscle energy technique and Kinesio taping showed significant improvement in VAS, Goniometer, and NDI in mechanical neck pain patients, making them suitable for inclusion in mechanical neck pain treatment.